PEMBELAJARAN MENULIS TEKS PUISI RAKYAT BERDASARKAN KURIKULUM 2013 SISWA KELAS VII MTS MIFTAHUL HUDA - Khafifah, Khafifah; Syambasril, Syambasril; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research is motivated by the curiosity of researcher towards the learning process of the text poetry people (pantun) in class VII of MTs Miftahul Huda in Landak Regency. The research was conducted by teacher who teaches in class VII. Researcher chose the research focus on 2013 curriculum based learning, including the planning, implementation, and the results of the text poetry people learning. This study describes Indonesian language teachers lesson plan, Implementation, and evaluated teaching learning achieved Teaching and Learning Wrote the Text Poetry People (pantun) Based on the 2013 Curriculum to the Seventh Grade of Miftahul Huda Landak Regency. The method used in this study is descriptive in the from qualitative research. The data sources of this study were Indonesian language subject teacher and seventh grade, they were 22 students. The date in this study are in the form of planning, implementation, and the result of teaching learning the text poetry people. Data collection techniques used in this study were observation, documentation, and interview. Meanwhile, data collection tools are observation guidelines, interview guidelines, and recording devices. Data analysis in this study includes three stages, namely: data reduction, data presentation, and data inference.Keywords: Poetry People, Teaching Learning, 2013 Curriculum